VARIATION IN SOME FLEECE COMPONENTS OVER THE BODY OF HAMADANI SHEEP - Kasim O. Aziz (Mesopotamia Journal of Agriculture)
The variation in some fiber properties at five sites / positions (shoulder, mid-side, hip, back and rump) over the body of Hamadani sheep were studied with 41 ewes. Staple length, fiber diameter, percentage of innercoat fibers and percentage of outercoat fibers were affected significantly (P ≤ 0.01) by sampling site. Although, the pattern of variation was not consistent, the wool at hip position was longer and coarser than that from shoulder or mid-side positions. The shortest, finest and highest percentage of innercoat fibers were found on the back site. Since the mid-side position showed intermediate values among other four positions together with it’s closer relations to the overall mean. Hence, the best compromise would be the use of mid-side position as the most suitable site for sampling Hamadani sheep fleeces.